Identification of New Approaches to Information Technology-Based Teaching for Successful Teaching of Millennial Generation Entering 21st Century Education - Ignatius Septo Pramesworo; Darmawanta Sembiring; Mohamad Sarip; Enos Lolang; Irwan Fathurrochman (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The millennial generation presents challenges and opportunities for educational institutions, including Perbanas Institute in Jakarta. To effectively educate millennials entering the 21st century, it is crucial to implement new approaches to information technology-based teaching that caters to their unique characteristics and learning preferences. This abstract summarizes the essential findings and recommendations regarding these new approaches. A comprehensive literature review has identified that gamification, blended learning, adaptive learning technologies, and online collaboration platforms effectively engage millennial learners and maximize their learning outcomes. Gamification incorporates game elements to motivate learners through rewards and interactive experiences. Blended learning combines online and face-to-face instruction, providing flexibility and personalized learning experiences. Adaptive learning technologies customize learning based on individual needs, while online collaboration platforms promote collaboration and effective communication skills. To successfully implement these new approaches, Perbanas Institute should invest in faculty development programs, upgrade technological infrastructure, and foster a culture of innovation and collaboration. Faculty members need the training to integrate technology effectively, while students require the necessary resources and support. By embracing these new approaches, Perbanas Institute can enhance the educational experiences of millennial learners and equip them with the skills required for the 21st-century workforce. Aligning teaching methods with the needs and preferences of millennials will prepare them for the evolving digital landscape and ensure their future success. Keywords: Technology-Based Teaching, Teaching of Millennial Generation, Succesfull Teaching